The transformation of emotion : First and third person perspectives in developmental context - YIP, Brandon (Institutional Knowledge at Singapore Management University, 2023)
Shun argues that the distinction made between emotions experienced from the first-person perspective and those from the third-person perspective does not capture our everyday emotional experience. My proposal is that even if we accept this claim, first- and third-person perspective taking is still crucial in the development of our emotional psychology. This is so in two respects. First, the features of intimacy and impartiality that mark adult emotional response are a product of a developmental process that involves perspective taking. Second, perspective taking is a crucial part of refining and developing virtuous emotional responses.